2000
DOI: 10.1046/j.1471-4159.2000.0741685.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Adenylyl Cyclase, ERK1/2, and CREB by Gz Following Acute and Chronic Activation of the δ‐Opioid Receptor

Abstract: Opioid tolerance and physical dependence in mammals can be rapidly induced by chronic exposure to opioid agonists. Recently, opioid receptors have been shown to interact with the pertussis toxin (PTX)-insensitive G z (a member of the G i subfamily), which inhibits adenylyl cyclase and stimulates mitogen-activated protein kinases (MAPKs). Here, we established stable human embryonic kidney 293 cell lines expressing ␦-opioid receptors with or without G z to examine the role of G z in opioid receptor-regulated sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 40 publications
4
40
0
Order By: Relevance
“…Failure of PKA inhibitors to modify acute morphine analgesia also supports the notion that cAMP effectors are minimally involved in the acute analgesic responses to opioids (Bernstein and Welch, 1999), as does the observation that phosphodiesterase inhibitors do not modify analgesia caused by intracerebroventricular or intrathecal administration of DPDPE (Suh et al, 1995). On the other hand, cAMP signaling has been consistently implicated in cellular adaptations that result from sustained DOPr stimulation and may contribute to analgesic tolerance (Tso et al, 2000;Varga, 2003;Zhang et al, 2006). These adaptations generally involve an increase in AC catalytic activity, although the mechanisms contributing to such an increase vary according to the type of AC involved (Avidor-Reiss et al, 1997;Varga, 2003).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Failure of PKA inhibitors to modify acute morphine analgesia also supports the notion that cAMP effectors are minimally involved in the acute analgesic responses to opioids (Bernstein and Welch, 1999), as does the observation that phosphodiesterase inhibitors do not modify analgesia caused by intracerebroventricular or intrathecal administration of DPDPE (Suh et al, 1995). On the other hand, cAMP signaling has been consistently implicated in cellular adaptations that result from sustained DOPr stimulation and may contribute to analgesic tolerance (Tso et al, 2000;Varga, 2003;Zhang et al, 2006). These adaptations generally involve an increase in AC catalytic activity, although the mechanisms contributing to such an increase vary according to the type of AC involved (Avidor-Reiss et al, 1997;Varga, 2003).…”
mentioning
confidence: 56%
“…In immortalized cell lines expressing either endogenous or recombinant DOPr, Gai2 has been frequently associated with cAMP inhibition, although additional subtypes are also involved in this response (Table 4). For example, DOPrs expressed in Chinese hamster ovary (CHO), COS cells (George et al, 2000;Fan et al, 2005), and HEK293 cells (Tsu et al, 1997;Tso et al, 2000) activate Gaz and modulate AC activity in a PTXinsensitive manner. In COS and CHO cells, AC inhibition by DOPr agonists was only evident when these receptors were coexpressed with MOPrs (George et al, 2000); however, in HEK cells, DOPrs expressed by themselves were able to both inhibit (Tsu et al, 1997;Ho and Wong, 2000;Tso et al, 2000) or stimulate cAMP production via Gaz (Tsu et al, 1997;Ho et al, 2001).…”
Section: A D-opioid Receptors and Adenylate Cyclase Signalingmentioning
confidence: 99%
“…It has been previously demonstrated that ␦-or -ORs expressed in HEK293 cells or Rat-1 fibroblasts stimulate ERK1/2 activity via PTX-sensitive or -insensitive G protein signaling mechanisms (Burt et al, 1996;Tso et al, 2000;Belcheva et al, 2002). To examine whether the ␦-i3L peptide can be also used as potential inhibitor of this type of GPCR signaling, ERK activation was measured in response to ␦-and -opioid agonist stimulation in serum-starved HEK293 cells expressing these receptors.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Cells were assayed for ERK and JNK activities as previously described [36,37]. Briefly, cells were challenged with chemokines and the cell contents were extracted, separated by SDS-PAGE, and transferred to nitrocellulose membrane before incubation with antisera against phospho-ERK1/2 or phospho-JNK and detection using the ECL kit.…”
Section: Western Blotting Analysis and Mapk Assaysmentioning
confidence: 99%